2015
DOI: 10.1007/s10900-015-9997-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hearing Healthcare in Kentucky’s Appalachian Primary Care Setting

Abstract: Objective Diagnosis and intervention for infant hearing loss is often delayed in areas of healthcare disparity, such as rural Appalachia. Primary care providers play a key role in timely hearing healthcare. The purpose of this study was to assess the practice patterns of rural primary care providers (PCPs) regarding newborn hearing screening (NHS) and experiences with rural early hearing diagnosis and intervention (EHDI) programs in an area of known hearing healthcare disparity. Study design Cross sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Disparities were most commonly reported in the realm of otology (33 of 61 [54.1%] studies). Examples of otologic disparities included decreased parental knowledge of failed newborn‐hearing screens and lower likelihood of audiology follow‐up testing for infant hearing‐loss patients in more rural compared to less rural areas . Several disparities related to acute otitis media (AOM), including a higher risk of AOM in low SES patients, longer wait times for AOM treatment for Medicaid versus private insurance patients, and lower likelihood of affording medications or seeing a specialist for frequent ear infections in black and Hispanic versus white patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities were most commonly reported in the realm of otology (33 of 61 [54.1%] studies). Examples of otologic disparities included decreased parental knowledge of failed newborn‐hearing screens and lower likelihood of audiology follow‐up testing for infant hearing‐loss patients in more rural compared to less rural areas . Several disparities related to acute otitis media (AOM), including a higher risk of AOM in low SES patients, longer wait times for AOM treatment for Medicaid versus private insurance patients, and lower likelihood of affording medications or seeing a specialist for frequent ear infections in black and Hispanic versus white patients .…”
Section: Resultsmentioning
confidence: 99%
“…Examples of otologic disparities included decreased parental knowledge of failed newborn-hearing screens and lower likelihood of audiology follow-up testing for infant hearingloss patients in more rural compared to less rural areas. 21,22 Several disparities related to acute otitis media (AOM), including a higher risk of AOM in low SES patients, longer wait times for AOM treatment for Medicaid versus private insurance patients, and lower likelihood of affording medications or seeing a specialist for frequent ear infections in black and Hispanic versus white patients. 16,[23][24][25] Of note, in one study controlling for type of insurance, children of color with recurrent ear infections still had a lower chance of seeing a specialist and a higher chance of having delayed care due to transportation difficulties compared to their white counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Resources such as telemedicine could directly address some of the distance concerns for some of the participants [17]. Nearly all of the study participants welcomed the idea of telemedicine, and a few reported they already utilize it for other aspects of their child’s care.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional survey of 93 rural physicians, many providers reported that they do not receive newborn hearing screening results consistently and they lack confidence in counseling parents through the EHDI process. 54 …”
Section: Barriers To Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%